MPK3/MPK6 are involved in iron deficiency-induced ethylene production in Arabidopsis - Ye, Lingxiao; Li, Lin; Wang, Lu; Wang, Shoudong; Li, Sen; Du, Juan; Zhang, Shuqun; Shou, Huixia (Frontiers in Plant Science, 2015)
Iron (Fe) is an essential micronutrient that participates in various biological processes important for plant growth. Ethylene production induced by Fe deficiency plays important roles in plant tolerance to stress induced by Fe deficiency. However, the activation and regulatory mechanisms of 1-Aminocyclopropane-1-carboxylic acid synthase (ACS) genes in this response are not clear. In this study, we demonstrated that Fe deficiency increased the abundance of ACS2, ACS6, ACS7, and ACS11 transcripts in both leaf and root as well as the abundance of ACS8 transcripts in leaf and ACS9 transcripts in root. Furthermore, we investigated the role of mitogen-activated protein kinase 3 and 6 (MPK3/MPK6)-regulated ACS2/6 activation in Fe deficiency-induced ethylene production. Our results showed that MPK3/MPK6 transcript abundance and MPK3/MPK6 phosphorylation are elevated under conditions of Fe deficiency. Furthermore, mpk3 and mpk6 mutants show a lesser induction of ethylene production under Fe deficiency and a greater sensitivity to Fe deficiency. Finally, in mpk3, mpk6, and acs2 mutants under conditions of Fe deficiency, induction of transcript expression of the Fe-deficiency response genes FRO2, IRT1, and FIT is partially compromised. Taken together, our results suggest that the MPK3/MPK6 and ACS2 are part of the Fe starvation-induced ethylene production signaling pathway.